Effective Treatment of Invasive Aspergillus fumigatus Infection Using Combinations of Topical and Systemic Antifungals in a Severely Burned Patient. Issue 2 (March 2015) - Fournier, Anne; Pantet, Olivier; Guerid, Samia; Eggimann, Philippe; Pagani, Jean-Luc; Revelly, Jean-Pierre; Hauser, Philippe M.; Marchetti, Oscar; Fontanella, Sara; Letovanec, Igor; Ravat, François; Berger, Mette M.; et al.
<x xml:space="preserve">Abstract</x> The authors describe an invasive Aspergillus fumigatus deep-burn wound infection in a severely burned patient that was successfully treated with a combination of topical terbinafine and systemic voriconazole antifungal therapy. To our knowledge, this is the first case report describing the effective control of an invasive deep-burn wound infection using this combination.